Tetraploids expanded beyond the mountain niche of their diploid ancestors in the mixed-ploidy grass Festuca amethystina L. - Kiedrzyński, Marcin; Zielińska, Katarzyna M.; Jedrzejczyk, Iwona; Kiedrzyńska, Edyta; Tomczyk, Przemysław P.; Rewicz, Agnieszka; Rewers, Monika; Indreica, Adrian; Bednarska, Iryna; Stupar, Vladimir; Roleček, Jan; Šmarda, Petr (Springer Science and Business Media LLC, 2021)
One promising area in understanding the responses of plants to ongoing global climate change is the adaptative effect of polyploidy. This work examines whether there is a coupling between the distribution of cytotypes and their biogeographical niche, and how different niches will affect their potential range. The study uses a range of techniques including flow cytometry, gradient and niche analysis, as well as distribution modelling. In addition, climatic, edaphic and habitat data was used to analyse environmental patterns and potential ranges of cytotypes in the first wide-range study of Festuca amethystina—a mixed-ploidy mountain grass. The populations were found to be ploidy homogeneous and demonstrate a parapatric pattern of cytotype distribution. Potential contact zones have been identified. The tetraploids have a geographically broader distribution than diploids; they also tend to occur at lower altitudes and grow in more diverse climates, geological units and habitats. Moreover, tetraploids have a more extensive potential range, being six-fold larger than diploids. Montane pine forests were found to be a focal environment suitable for both cytotypes, which has a central place in the environmental space of the whole species. Our findings present polyploidy as a visible driver of geographical, ecological and adaptive variation within the species.
Keywords: Evolutionary ecology; predictive modelling; ploidy level; cytotypes; glacial relicts; suitable habitats